Real exchange rate misalignment and economic growth in Nigeria (1960-2011) - Waheed Ibrahim (CBN Journal of Applied Statistics, 2016)
This paper examines the impact of real effective exchange rate misalignment on economic growth in Nigeria using an annual data spanning 1960 to 2011. The augmented growth model was estimated using purchasing power parity (PPP) and generalized method of moment (GMM) approaches. Through series of iterative processes, it was observed that it will take four years for the exchange rate to revert back to equilibrium. The result from the PPP approach shows that the period of flexible exchange rate regime is characterized by a relatively lower real exchange rate misalignment over time compared with the fixed exchange rate regime. The GMM estimate reveals that real exchange rate misalignment has negative but significant impact on economic growth over the period under consideration. In view of the findings, the study recommends appropriate exchange rate to minimize the problem of exchange rate misalignment and to ensure sustainable economic growth over time.
Keywords: O40; F31; 330; Effective Exchange Rate; PPP; Misalignment; GMM; Flexible and Fixed; economic growth